Bahasa Indonesia: Policy, Implementation, and Planning - Risa R. Simanjuntak (Bina Nusantara University, 2009)
Language policy or language planning is still in the surge for familiarity and importance. However, this paper argues that in the case of Bahasa Indonesia current implementations should be evaluated based on its relevance and future plan. The historical perspectives will reveal the roots of the current policy and therefore make foundations for further discussions. From the study of literature, this paper is arguing that new paradigm for nationalism, roles in the global competition, as well as regional languages as competitive advantage could be well adopted to nurture a more inclusive and progressive Bahasa Indonesia.